The Effect Of Price Earning Ratio (Per), Return On Equity (Roe), And Earning Per Share (Eps) On Stock Prices In Pt Indocement Tunggal Prakarsa Tbk - Napitupulu, Hotma (Technium Social Sciences Journal, 2022)
This study aims to analyze the effect of Price Earning Ratio (PER), Return On Equity (ROE) and Earning Per Share (EPS) on the share price of PT Indocement Tunggal Prakarsa. Data were analyzed using multiple linearregression analysis secondary data with SPSS 25 software sourced from the financial statements of PT Indocement Tunggal Prakarsa for the period 2013-2020. The results of t-test research show that Price Earning Ratio (PER) and Earning Per Share (EPS) has a significant positive effect on stock prices, while the Return On Equity (ROE) variables have a significant negative effect on stock prices. The results of the F test show that the Price Earninf Ratio (PER), Return On Equity (ROE) and Earning Per Share (EPS) simultaneously have a significant effect on stock prices.